2016
DOI: 10.1186/s12985-016-0598-z
|View full text |Cite
|
Sign up to set email alerts
|

Responses of primary human nasal epithelial cells to EDIII-DENV stimulation: the first step to intranasal dengue vaccination

Abstract: BackgroundAbout half of the world’s population are living in the endemic area of dengue viruses implying that a rapid-mass vaccination may be required. In addition, a major target of dengue vaccine are children, thus, a needle-free administration is more attractive. These problems may be overcome by the alternative route of vaccination such as topical, oral and intranasal vaccination. Here, we investigated the possibility to deliver a dengue immunogen intranasally, a painless route of vaccination. The tested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…The particles uptake by DCs also upregulated the maturation markers (CD80, CD83, CD86, and HLA-DR) of DCs. 107 Similar uptake and upregulation of maturation markers CD83, CD86, and MHC-II was reported by a separate group. 89 In another study, TMC-coated PLGA NPs and TMC-TPP NPs enhanced the antigen presentation by DCs, as shown by increased in vitro and in vivo CD4 + T-cell proliferation.…”
Section: Particulate Effectsupporting
confidence: 76%
See 1 more Smart Citation
“…The particles uptake by DCs also upregulated the maturation markers (CD80, CD83, CD86, and HLA-DR) of DCs. 107 Similar uptake and upregulation of maturation markers CD83, CD86, and MHC-II was reported by a separate group. 89 In another study, TMC-coated PLGA NPs and TMC-TPP NPs enhanced the antigen presentation by DCs, as shown by increased in vitro and in vivo CD4 + T-cell proliferation.…”
Section: Particulate Effectsupporting
confidence: 76%
“…According to previous studies, TMC stimulates the DCs and APCs and even caused the maturation and differentiation of these cells, simultaneously releasing several cytokines. For instance, Nantachit et al 107 demonstrated that the in vitro stimulation of human nasal epithelial cells with TMC NPs encapsulating EDIII-D3 (domain III of dengue serotype-3 E protein) stimulated the secretion of several proinflammatory, Th1, and Th2 cytokines as well as chemokines. The particles uptake by DCs also upregulated the maturation markers (CD80, CD83, CD86, and HLA-DR) of DCs.…”
Section: Particulate Effectmentioning
confidence: 99%
“…route was relatively higher compared to that in the intraperitoneally and intradermally infected groups. In general, the i.n immunization route favors the induction of strong immune responses with vaccine candidates against some important flaviviruses in human medicine [55,56]. The relatively high inoculation volume likely resulted in some of the virus dripping into the oropharynx and lungs, which could have also contributed to the enhanced dissemination of the virus and antibody response induced by this route.…”
Section: Discussionmentioning
confidence: 99%
“…This form of candidate dengue vaccine stimulated robust immune responses in a mouse model and proved very immunogenic in human MoDCs . In this study, we explored the immunogenicity of EDIII‐D3 encapsulated into adjuvant nanospheres, having recently reported that EDIII‐D3 administered via a nanosphere delivery system powerfully stimulates mucosal epithelial cell responses .…”
Section: Discussionmentioning
confidence: 99%